Age of the Angulos W-Mo mineralization from the Paimán Range (NW Argentina) and its geological significance - Sardi, Fernando Guillermo (2012)
The Angulos W-Mo-bearing ore deposit is located in the center-eastern region of the Famatina System, NW Argentina. The W-Mo mineralization in Angulos is genetically associated with the Potrerillos Granite, which is the host rock of the deposit. Re-Os isotopic dating on two molybdenites of the Angulos deposit yielded ages of 469.9 ± 1.6 and 464.8 ± 1.6 Ma (Middle Ordovician). The results are considered as the age of the mineralization and are contemporary with the age of the voluminous regional magmatism developed in the Famatina System. However, they are not in concordance with a previous Rb-Sr age of ~380 Ma for the Potrerillos Granite.